A Pilot Study of Serum MicroRNAs Panel as Potential Biomarkers for Diagnosis of Nonalcoholic Fatty Liver Disease - Tan, Youwen; Ge, Guohong; Pan, Tengli; Wen, Danfeng; Gan, Jianhe (PLOS ONE, 2014)
Background The invasive nature of liver biopsy makes the histopathological diagnosis of non-alcoholic fatty liver disease (NAFLD) difficult and its diagnostic performance unsatisfactory. The present study aimed to identify a serum microRNA (miRNA) expression profile that could serve as a novel diagnostic biomarker for NAFLD. Methods Serum miRNA expression was investigated using three cohorts comprising 465 participants (healthy controls and NAFLD patients) recruited between August 2010 and June 2013. miRNA expression was initially screened by Illumina sequencing using serum samples pooled from 20 patients and 20 controls. Quantitative reverse transcriptase polymerase chain reaction assay was then used to evaluate the expression of selected miRNAs. A logistic regression model was constructed using a training cohort (n = 242) and validated using another cohort (n = 183). The area under the receiver operating characteristic curve (AUC) was used to evaluate diagnostic accuracy. Results We identified an miRNA panel (hsa-miR-122-5p, hsa-miR-1290, hsa-miR-27b-3p, and hsa-miR-192-5p) with a high diagnostic accuracy for NAFLD. The satisfactory diagnostic performance of the miRNA panel remained regardless of the NAFLD activity score (NAS) status. There was significant difference between the AUC values of the miRNA panel and those of ALT (AUC = 0.786, 95% CI = 0.717–0.855; P = 0.142) and FIB-4 (AUC = 0.795, 95% CI = 0.730–0.860; sensitivity = 69.9%, specificity = 83.7%. Conclusion We identified a serum microRNA panel with considerable clinical value in NAFLD diagnosis. The results indicate that the miRNA panel is a more sensitive and specific biomarker for NAFLD than ALT and FIB-4.